SOCIAL MEDIA BEAUTY MARKETING IN SHANGHAI: HOW INTERNET CELEBRITY CHARACTERISTICS AND SOCIAL COMPARISON DRIVE PURCHASE INTENTIONS THROUGH FOMO - Liu, Tingxuan; Bunchapattanasakda, Chanchai (Asian Administration and Management Review, 2025)
This study examines the intricate relationship between internet celebrity characteristics, social comparison, fear of missing out (FOMO), and beauty product purchase intentions among Shanghai residents on social media. Through quantitative survey data and structural equation modeling, the research reveals that internet celebrity reputation, image consistency, and interactivity have a significant impact on consumer decisions, with FOMO acting as a key mediator. Notably, a reputable influencer fosters trust, image consistency enhances authenticity, and interactivity deepens emotional bonds, all of which drive purchase behaviors. Results confirm that social comparison amplifies FOMO. Suggesting effective strategies: build credible influencers, a consistent image, and leverage FOMO. In summary, the results contribute to the understanding of social learning theory.